Fuzzy Logic Algorithm of Sugeno Method for Controlling Line Follower Mobile Robot - Aji, Bayu; Sutikno, Sutikno (ILKOM Jurnal Ilmiah, 2023)
The industrial world has been increasingly using robots for production purposes. One type of robot used is a line follower robot for the purposes of transportation of production materials. Various researches and competitions of line follower robots were held to improve its performance. This study proposed a fuzzy logic algorithm using Sugeno method for a line follower mobile robot. This algorithm received input from the readings of 8 sensors mounted on the bottom of the robot and generated the speed of each left and right motor. This speed was used to keep the robot on track. The performance of this algorithm was compared with the fuzzy logic algorithm of the Mamdani method. The proposed fuzzy logic algorithm was better in terms of speed. The results of this study can be used as material to study the application of fuzzy logic algorithm in real time.